Ara Yüzey Dislokasyonları - Cihan, Tuğba (Ondokuz Mayıs Üniversitesi, Fen Bilimleri Enstitüsü, 2008)
Mekanik zor etkisiyle birbirlerine göre kısmen dönmüş veya zorlanmış kristallerin ara sınır yüzeylerinin durumunu inceleyeceğiz.Ara sınır yüzeylerinde bu deformasyonun analitik hesaplamaları bu tezde yapılıyor olup sınır yüzeyinde uyum ve uyumsuzluk noktaları olarak ortaya çıkıyor ki bu noktaların üç, iki veya tek boyutta geometrik yerleri Moiré desenleri olarak tanımlanır.Moiré desenlerinin geometrik konumları dönüşüm matrislerinin determinant ve rankından bulunabilir.Anahtar Kelimeler: 0-Örgüsü, Moiré Deseni, Faz Sınırı

We shall investigate the case a boundary between two joined crystals of the same kind,but slightly rotated or deformed with respect to one another by effect mechanical stresses .In this thesis, the analytic calculations of this defor mations are made, there are being points of best and goodfit on the grain boundary plane. That points called as 0-lattice points (Coincidense Lattice Points, CSL) and the geometric positions of that points are describe the Moiré pattern with three, two and one dimension.The geometric position of this Moiré patterns can be found from the determinant and the rank of the transformation matrixes.Key Words: 0-Lattice, Moiré Pattern, Grain Boundary
Interface Dislocations
Tez (yüksek lisans) -- Ondokuz Mayıs Üniversitesi, 2008
Libra Kayıt No: 65181
Keywords: Physics and Physics Engineering; Fizik ve Fizik Mühendisliği; TEZ YÜK LİS C571a 2008